Virtue Quadratic Male Sling for stress incontinence—surgical guide for placement and delayed revision - Rubin, Rachel S.; Xavier, Keith R.; Rhee, Eugene (Translational Andrology and Urology; Vol 6, No 4 (August 12, 2017): Translational Andrology and Urology (Technique and Complications from the Masters in Andrologic Surgery), 2017)
The algorithm for surgical management of post prostatectomy incontinence classically includes male slings and artificial urinary sphincter (AUS) placement. The Virtue Quadratic Male Sling was designed to provide both urethral elevation and prepubic compression making it a viable option for a wider spectrum of incontinent men whose symptoms range from mild to severe. With a focus on two key steps of the surgery, (I) sling fixation (II) use of intraoperative retrograde leak point pressure (RLPP), this guide is intended to outline a safe and efficacious treatment for post-prostatectomy incontinence. Intriguingly, the sling can be revised in the event of refractory or worsening leakage, and does not preclude the placement of an AUS should it be needed. This paper describes a step by step approach to performing the procedure as well as expert tips to improve outcomes and avoid/manage complications that have been learned over the years.